CONSTANS Imparts DNA Sequence Specificity to the Histone Fold NF-YB/NF-YC Dimer. Issue 6 (19th May 2017) - Gnesutta, Nerina; Kumimoto, Roderick W.; Swain, Swadhin; Chiara, Matteo; Siriwardana, Chamindika; Horner, David S.; Holt, Ben F.; Mantovani, Roberto
Abstract : CONSTANS forms a trimeric complex with At-NF-YB2/NF-YC3 to efficiently bind the CORE element: the CCT provides trimerization and DNA-binding, akin to NF-YA but divergent in sequence selectivity. Abstract: Nuclear Factor Y (NF-Y) is a heterotrimeric transcription factor that binds CCAAT elements. The NF-Y trimer is composed of a Histone Fold Domain (HFD) dimer (NF-YB/NF-YC) and NF-YA, which confers DNA sequence specificity. NF-YA shares a conserved domain with the CONSTANS, CONSTANS-LIKE, TOC1 (CCT) proteins. We show that CONSTANS (CO/B-BOX PROTEIN1 BBX1), a master flowering regulator, forms a trimer with Arabidopsis thaliana NF-YB2/NF-YC3 to efficiently bind the CORE element of the FLOWERING LOCUS T promoter. We term this complex NF-CO. Using saturation mutagenesis, electrophoretic mobility shift assays, and RNA-sequencing profiling of co, nf-yb, and nf-yc mutants, we identify CCACA elements as the core NF-CO binding site. CO physically interacts with the same HFD surface required for NF-YA association, as determined by mutations in NF-YB2 and NF-YC9, and tested in vitro and in vivo. The co-7 mutation in the CCT domain, corresponding to an NF-YA arginine directly involved in CCAAT recognition, abolishes NF-CO binding to DNA. In summary, a unifying molecular mechanism of CO function relates it to the NF-YA paradigm, as part of a trimeric complex imparting sequence specificity to HFD/DNA interactions. It is likely that members of the large CCT family participate in similar complexes with At-NF-YB and At-NF-YC, broadening HFD combinatorial possibilities in terms of trimerization, DNA binding specificities, and transcriptional regulation.